PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP HASIL BELAJAR IPA SISWA KELAS V SDN 003 PELINTUNG KECAMATAN MEDANG KAMPAI - Ravita Dewi; Mahmud Alpusari; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The Issue of this research is whether there is a significant influence ofthe Quantum Teaching learning model towards natural science (IPA) achievement offifth grade students of SDN 003 Pelintung. This type of research is quasi experiment.The subject of research is the grade of V A and B. The number of the subject as muchas 44 students. The technique of data collection is done with the pre-loaded test,treatment with 3 times in class experiments using the Quantum teaching learning modeland post-test. The results showed that after implementing the model of Quantumteaching learning, the natural science (IPA) achievement of fifht grade studentsincreased based on hypothesis test of value of t calculate the resulting is 22, 711 >value of t table 2, 017 and value significance of 0, 000 from 0, 05 < stating that thehypothesis in this study was received. From the results it can be concluded that there isthe influence of the Quantum teaching learning model towards natural science (IPA)achievement of fifth grade students of SDN 003 Pelintung.Key Words: Quantum Teaching Learning Model, Science, Achievement